A stable tetraphenylethene derivative: aggregation-induced emission, different crystalline polymorphs, and totally different mechanoluminescence properties. Issue 3 (1st March 2016) - Wang, Can; Xu, Bingjia; Li, Mengshu; Chi, Zhenguo; Xie, Yujun; Li, Qianqian; Li, Zhen
Abstract : Two crystalline polymorphs of TMPE (Cp -form and Cc -form) exhibit totally different mechanoluminescence properties. Abstract : Two crystalline polymorphs of TMPE, with the space groups P 21 ( c ) and C 2, are cultured from different solvent mixtures and display apparent blue fluorescence with the characteristic of aggregation induced emission (AIE). Excitedly, the P 21 ( c ) crystal exhibits easily observed mechanoluminescence (ML), while there is no mechanoluminescence for the C 2 crystal. Careful investigation of their crystal structures and three analogues demonstrates that the special molecule packing of TMPE in the P 21 ( c ) crystal accounts for its exciting efficient ML performance, providing some information to understand the structure–property relationship of efficient organic ML materials.